2015
DOI: 10.1002/2015gl063872
|View full text |Cite
|
Sign up to set email alerts
|

Revised interpretation of recent InSAR signals observed at Llaima volcano (Chile)

Abstract: We analyzed C band and L band interferometric synthetic aperture radar (InSAR) data acquired from 2003 to 2011 to search for volcanic deformations at Llaima volcano, Southern Andes (38.69°S, 71.73°W). There, specific environmental conditions (steep slopes, snow‐ or ice‐capped summit, dense vegetation cover, and strong tropospheric artifacts) and limited amount of radar data available make it challenging to accurately measure ground surface displacement with InSAR. To overcome these difficulties, we first perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 40 publications
1
31
0
Order By: Relevance
“…We use InSAR data from the COSMO‐SkyMED (CSK), RADARSAT‐2 (RS2), Sentinel‐1 (S1), and ALOS‐2 missions to produce time series and differential interferograms that span the complete inflation events (Figures , and S1–S3; Table ). These data sets were processed with standard algorithms described in detail in the supporting information (Agram et al, ; Chen and Zebker, ; Delgado et al, ; Farr et al, ; Fattahi et al, ; Fattahi and Amelung, ; Finnegan et al, ; Goldstein and Werner, ; Lopez‐Quiroz et al, ; Prats‐Iraola et al, ; Remy et al, ; Rosen et al, ; Samsonov, ; Sansosti et al, ; Yague‐Martinez et al, ; Zebker et al, ).. The differential interferograms calculated for every satellite orbit show ∼12 cm of uplift between June 2016 and February 2017 (Figures c to i), with a mean velocity of ∼23 cm/year (Figure ), in agreement with an independent ALOS‐2 ScanSAR time series (Euillades et al, ).…”
Section: Insar Data and 2016–2018 Ground Deformationmentioning
confidence: 99%
“…We use InSAR data from the COSMO‐SkyMED (CSK), RADARSAT‐2 (RS2), Sentinel‐1 (S1), and ALOS‐2 missions to produce time series and differential interferograms that span the complete inflation events (Figures , and S1–S3; Table ). These data sets were processed with standard algorithms described in detail in the supporting information (Agram et al, ; Chen and Zebker, ; Delgado et al, ; Farr et al, ; Fattahi et al, ; Fattahi and Amelung, ; Finnegan et al, ; Goldstein and Werner, ; Lopez‐Quiroz et al, ; Prats‐Iraola et al, ; Remy et al, ; Rosen et al, ; Samsonov, ; Sansosti et al, ; Yague‐Martinez et al, ; Zebker et al, ).. The differential interferograms calculated for every satellite orbit show ∼12 cm of uplift between June 2016 and February 2017 (Figures c to i), with a mean velocity of ∼23 cm/year (Figure ), in agreement with an independent ALOS‐2 ScanSAR time series (Euillades et al, ).…”
Section: Insar Data and 2016–2018 Ground Deformationmentioning
confidence: 99%
“…In the absence of surface deformation, and after the mitigation of the ionospheric and hydrostatic phase signals (Hanssen, ; Kinoshita et al, ; Mateus, Nico, & Catalão, ; Mateus, Nico, Tomé, et al, ; Mateus et al, ; Remy et al, ; Wadge et al, ), InSAR images can be used to compute the spatial distribution of PWV, offering one of the few data sources with a horizontal resolution relevant for the atmospheric mesoscale. Its impact in short‐range numerical weather prediction was recently assessed in three studies.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated that, in the absence of surface displacements and processing artifacts (e.g., from inaccurate orbits or digital elevation model), and after removing the phase contribution due to ionospheric and hydrostatic temporal variations, the synthetic aperture radar (SAR) interferometry (InSAR) technique can be used to obtain maps of PWV temporal variations with high accuracy (1–2 mm) and spatial resolution (≤ 350 × 350 m obtained from the 5 × 20 m nominal resolution of Sentinel‐1 images) (Hanssen, ; Kinoshita et al, ; Mateus, Nico, Tomé, et al, ; Mateus, Nico, & Catalao, ; Remy et al, ; Wadge et al, ; Yun et al, ; Zebker et al, , etc.). These PWV maps can be used to better understand key relationships between water vapor spatial and temporal variabilities, the onset of convective cells at small scales, and their role in triggering precipitation, since InSAR measurements cover most of the spatial range of moist convection processes, down to the spatial resolution of C‐band SAR images of around 20 m. For example, Kinoshita et al () found that a convective system may contain a large amount of water vapor, with high spatial variations of PWV in small areas of up to 13 mm within 10 km.…”
Section: Introductionmentioning
confidence: 99%